Protein kinase C mediates hypoxia-induced long-term potentiation of NMDA neurotransmission in the visual retinocollicular pathway - Hanna Dumanska; Nikolai Veselovsky (Frontiers in Cellular Neuroscience, 2023)
The identification of processes and mechanisms underlying the early stage of hypoxic injury of the retinocollicular pathway may be beneficial for the future prevention and treatment of navigation, orientation, and visual attention impairments. Previously, we have demonstrated that short-term hypoxia led to long-term potentiation (LTP) of NMDA neurotransmission in the background of long-term depression of GABAA retinocollicular transmission. Here, we sought to obtain insight into the mechanisms of hypoxia-induced LTP of NMDA retinocollicular neurotransmission and the role of the protein kinase C (PKC) signaling pathway in it. To investigate these, we recorded pharmacologically isolated NMDA transmission in cocultivated pairs of rat retinal ganglion cells and superficial superior colliculus neurons under normoxic and hypoxic conditions, using the paired patch-clamp technique and method of fast local superfusion. We tested the involvement of the PKC by adding the potent and selective inhibitor chelerythrine chloride (ChC, 5 μM). We observed that hypoxia-induced LTP of NMDA neurotransmission is associated with the shortening of current kinetics. We also found that the PKC signaling pathway mediates hypoxia-induced LTP and associated shortening of NMDA currents. The ChC completely blocked the induction of LTP by hypoxia and associated kinetic changes. Contrary effects of ChC were observed with already induced LTP. ChC led to the reversal of LTP to the initial synaptic strength but the current kinetics remain irreversibly shortened. Our results show that ChC is a promising agent for the prevention and treatment of hypoxic injuries of NMDA retinocollicular neurotransmission and provide necessary electrophysiological basics for further research.